(untitled) (Conference on English Language Teaching, 2023)
The purpose of this study was to determine the implementation of the Kahoot! application in developing Student’s Reading skill. Reading skill is one of the most influential skills in English language learning. Especially if it is associated with the 21st century learning, which requires students to have critical thinking skills. Critical thinking certainly cannot be separated from the insight that one has. In this case, reading skills need to be developed. Kahoot! has an advantage over other applications. This can be seen from the ease of access, many features that can help develop some skills in learning English, especially in reading skills. In this study, the researcher used literature review. The data was collected using finding, selecting, departing, and analyzing previous research. The findings of this research revealed that Kahoot! application gives positive contribution in improving students’ reading skills.